A top-down implementation of a dynamic management control system - as easy as it seemed? A case study of Sparebank 1 Nord Norge - Edvardsen, Robin; Søreide, Erling (Nord universitet, 2016)
Masteroppgave i bedriftsøkonomi - Nord universitet, 2016